Preparation and application of a composite adsorbent for volatile ester compounds in the atmosphere
By combining the polymetallic MOFs material with ionic liquid and mixing it with activated alumina and activated carbon, an efficient mixed adsorbent was prepared, which solved the problem of low adsorption efficiency of existing adsorbents on volatile ester compounds, and achieved efficient and stable adsorption effect.
Patent Information
- Application Number
- CN202411967915.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing adsorbents have low adsorption efficiency, low adsorption capacity or single adsorption targets, making it difficult to effectively remove ester compounds in the atmosphere.
The polymetallic MOFs material is coupled with ionic liquid, combined with activated alumina and activated carbon, and MOFs ionic liquid composite material is prepared to form a mixed adsorbent with high porosity, large specific surface area and good adsorption selectivity.
The adsorption capacity and adsorption efficiency of volatile ester compounds have been significantly improved, with adsorption efficiency up to more than 80%, and the penetration capacity has also been greatly improved. It is suitable for high-temperature and high-humidity environments.
Smart Images

Figure CN119751912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbents, and more specifically relates to the preparation and application of a composite adsorbent for volatile ester compounds in the atmosphere. Background Art
[0002] In the process of modern industrialization, ester compounds, as important organic chemical raw materials and intermediates, are widely used in many fields such as coatings, plastics, fragrances, and medicines. However, with the increase in the production and use of ester compounds, their volatilization and release in the atmospheric environment are becoming increasingly serious, leading to potential harm of air pollution to the ecological environment. Ester compounds not only pose a threat to human health, but may also cause long-term damage to the ecosystem. Therefore, the development of efficient gas adsorption materials to remove ester compounds in the atmosphere has become an important topic in current environmental science research.
[0003] When volatile ester compounds (such as ethyl acetate, ethyl formate, propyl formate, butyl acetate, etc.) are stored or used, a small amount of volatilization is often produced, resulting in a high level of VOCs in the atmospheric air. Adsorption is a simple and practical VOCs treatment technology, and is also an effective measure for VOCs management. The core of the adsorption method is the adsorbent. Currently, commonly used adsorbents include activated carbon, zeolite, activated alumina, silica gel, kaolin, and molecular sieves. Although these adsorbents have universal adsorption and good adsorption for most VOCs, they have problems such as low adsorption efficiency, low adsorption capacity, or a single adsorption target for volatile ester compounds. In order to further improve the adsorption capacity and efficiency of adsorbents specifically for volatile ester compounds, the development of new adsorbents or the modification of traditional adsorbents have become a difficult problem that technicians in this field need to overcome. Summary of the invention
[0004] The purpose of the present invention is to provide a composite adsorbent for the preparation and application of volatile ester compounds in the atmosphere, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a multi-metal MOFs material, comprising the following steps:
[0007] Cu 2+ , Mn 2+ and Zr 4+ To coordinate the metal, aminophthalic acid is used as the organic ligand, and a multi-metal MOFs material is obtained through a solvent thermal reaction.
[0008] The multi-metal MOFs material prepared by the present invention is a MOFs material with Cu / Zr / Mn as the metal center.
[0009] Furthermore, the Cu 2+ , Mn 2+ and Zr 4+ The molar ratio is 1:0.5-1.2:0.05-0.4.
[0010] Furthermore, the Cu 2+ Derived from at least one of nitrate, hydrochloride, sulfate and acetate of copper.
[0011] Furthermore, the Mn 2+ Derived from at least one of the nitrate, sulfate, hydrochloride and acetate of manganese.
[0012] Furthermore, the Zr 4+ Derived from at least one of zirconium hydrochloride, acetate, nitrate and zirconium hydroxide.
[0013] Furthermore, the molar ratio of the organic ligand to the coordinated metal is 1:0.5-3.0.
[0014] Furthermore, the temperature of the solvent thermal reaction is 60-100° C. and the time is 12-24 hours.
[0015] The multi-metal MOFs material prepared by the present invention has higher porosity, larger adsorption capacity and better stability compared with bimetallic and monometallic MOFs.
[0016] The second technical solution of the present invention: provides a multi-metal MOFs material, which is prepared by the above-mentioned preparation method.
[0017] The third technical solution of the present invention is to provide a MOFs ionic liquid composite material, the raw materials of which include the above-mentioned multi-metal MOFs material.
[0018] Technical solution 4 of the present invention: Provide a method for preparing the above-mentioned MOFs ionic liquid composite material, the steps comprising:
[0019] The multi-metal MOFs material and the ethanol solution of the ionic liquid are mixed evenly, reacted, and nitrogen blown to obtain a composite material;
[0020] The activated alumina and the activated carbon are uniformly mixed, and then ethanol is added, soaked, and nitrogen blown to obtain a mixture;
[0021] The composite material and the mixture are uniformly mixed, and the MOFs ionic liquid composite material is obtained through baking and cooling.
[0022] Furthermore, the dosage ratio of the multi-metal MOFs material and the ethanol solution of the ionic liquid is 100g:20-100mL.
[0023] Furthermore, the concentration of the ionic liquid in the ethanol solution of the ionic liquid is 1 to 5 g / 100 mL.
[0024] Furthermore, the ionic liquid in the ethanol solution of the ionic liquid is a nitrogen-containing heterocyclic ionic liquid.
[0025] Optionally, the nitrogen-containing heterocyclic ionic liquid includes at least one of 1-alkyl-3-methylimidazolium chloride, 1-alkyl-1,2,4-triazole sulfate, 1-alkyl-benzimidazole chloride and 1-pentyl-1,2,3-benzotriazole sulfate.
[0026] Furthermore, the reaction is carried out under shaking conditions at 60-80° C. for 12-24 hours.
[0027] In the above scheme, the selection of ionic liquid and its coating on the surface of MOFs material can improve the stability of MOFs material and improve the adsorption efficiency of various volatile ester compounds. The mass ratio of metal MOFs material and ionic liquid is 100:0.5-5.0.
[0028] Furthermore, the mass ratio of the activated alumina to the activated carbon is 0.2-1:0.1-2.
[0029] Furthermore, the particle size of the activated alumina is 10-40 μm.
[0030] Furthermore, the porosity of the activated carbon is 0.6-0.9 cm 3 / g, particle size is 0.2-0.5mm.
[0031] Furthermore, the mass / volume ratio of the sum of the masses of the activated alumina and the activated carbon to ethanol is 100g / 20-100mL.
[0032] Furthermore, the soaking treatment is performed by shaking and soaking at 30-50° C. for 12-24 hours.
[0033] In the above scheme, activated alumina and activated carbon can further improve the recovery rate of volatile esters in the adsorption tube.
[0034] Furthermore, the mass ratio of the composite material to the mixture is 1:1-5.
[0035] Furthermore, the baking temperature is 50-150° C. and the baking time is 1-3 hours.
[0036] In the present invention, baking and cooling are both carried out under nitrogen protection.
[0037] The fifth technical solution of the present invention: provides an application of the above-mentioned multi-metal MOFs material or the above-mentioned MOFs ionic liquid composite material in the adsorption of volatile ester compounds.
[0038] Technical solution six of the present invention: Provide a volatile ester compound adsorbent, the raw materials of which include the above-mentioned MOFs ionic liquid composite material.
[0039] The present invention discloses the following technical effects:
[0040] The present invention provides a multi-metal MOFs material, which is a MOFs material with Cu / Zr / Mn as the metal center. The MOFs ionic liquid composite material is prepared by coupling the MOFs ionic liquid composite material with ionic liquid, and then mixed with activated alumina and activated carbon to prepare a MOFs ionic liquid-alumina-activated carbon mixed adsorbent. The mixed adsorbent has high porosity (up to 55%), high specific surface area (up to 5500m 2 / g), and adsorption selectivity. When used to remove or collect volatile ester compounds in the air, it has a higher adsorption capacity (up to 31.2 mg / 100 g for ethyl acetate) and a higher adsorption efficiency (up to more than 80%), which significantly improves the removal or collection efficiency.
[0041] The novel mixed adsorbent of the present invention not only improves the adsorption effect on volatile straight-chain alkane ester compounds, but also further improves the adsorption effect on volatile lactone compounds due to the reasonable addition of MOFs material nitrogen-containing heterocyclic compound ionic liquid.
[0042] The volatile ester compound adsorbent prepared by the method of the present invention has significantly improved penetration capacity for ester compounds, and the penetration capacity per 100g is respectively: methyl formate (3.1mg), ethyl formate (14.5mg), methyl acetate (7.6mg), ethyl acetate (31.2mg), propyl acetate (29.6mg), butyl acetate (41.3mg), pentyl acetate (29.2mg), 1,4-butyrolactone (4.8mg). The adsorbent reported in the literature (GBZ160.63-2007) has the penetration capacity per 100g as follows: methyl formate (2.1mg), ethyl formate (8.4mg), methyl acetate (2.9mg), ethyl acetate (14.6mg), propyl acetate (24.5mg), butyl acetate (32.1mg), pentyl acetate (21.0mg), 1,4-butyrolactone (1.2mg).
[0043] The volatile ester compound adsorbent and MOFs ionic liquid composite material of the present invention are moisture-resistant and high-temperature-resistant, and the adsorption efficiency of each volatile ester compound can still reach more than 90% in an environment with a temperature greater than 30°C and a humidity greater than 80RH%. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0045] Figure 1 This is a physical picture of the adsorption-desorption tube prepared in the test example.
[0046] Figure 2 This is the SEM image of the multi-metal MOFs material with Cu / Zr / Mn as the metal center prepared in Example 1.
[0047] Figure 3 This is a thermogravimetric analysis (TGA) graph of the mixed adsorbent of the MOFs ionic liquid composite material prepared in Example 1.
[0048] Figure 4 This is the gas chromatography hydrogen flame ionization detector chromatogram of the standard solution of volatile ester compounds, 1: methyl formate, 2: ethyl formate, 3: 1,4-butyrolactone, 4: methyl acetate, 5: ethyl acetate, 6: propyl acetate, 7: butyl acetate, 8: pentyl acetate. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] Metal organic framework (MOFs) materials are a class of hybrid organic-inorganic supramolecular materials with the highest specific surface area, the lowest crystal density, and adjustable pore size and functional structure, which enable MOFs to achieve some special applications, including gas storage and separation, catalysis, and drug sustained release. By introducing functional groups into organic ligands or using MOFs as the main environment to introduce active components, the functionalized MOFs materials can be synthesized, which can greatly broaden its application range. The multi-metal MOFs material prepared by the present invention is coupled with a nitrogen-containing heterocyclic ionic liquid, and then mixed with activated alumina and activated carbon, and processed at 60-150°C to obtain a MOFs ionic liquid composite material (adsorbent), which improves the overall porosity, specific surface area and adsorption selectivity of the adsorbent, and also improves the adsorption efficiency and adsorption capacity of the adsorbent for ester compounds, and can be used for the efficient adsorption and desorption of volatile ester compounds commonly found in the atmospheric environment. The volatile ester compound adsorbent of the present invention utilizes the synergistic effect of multiple materials, has excellent adsorption performance and selectivity, can effectively remove ester compounds present in the atmosphere, is low-cost and environmentally friendly, and has made certain contributions to improving air quality and protecting the ecological environment.
[0055] The raw materials and reagents used in the specific embodiment of the present invention are all commercially available products. The activated alumina used is provided by Nanjing Chemical Reagent Co., Ltd., with specifications of: particle size 10-40 μm, specific surface area 60-90 m 2 / g; The activated carbon used was provided by Nanjing Chemical Reagent Co., Ltd., with the following specifications: porosity of 0.6-0.9cm 3 / g, particle size is 0.2-0.5mm.
[0056] Example 1
[0057] Preparation of MOFs ionic liquid composites:
[0058] S1, 100g Cu(NO 3 ) 2 ·3H 2 O, 60g Mn(NO 3 ) 2 ·4H2 O and 20 g ZrCl 4 After being mixed evenly, the mixture was dissolved in a mixed solution of 500 mL of hydrochloric acid solution (0.01 mol / L) and 500 mL of DMF, and then 90 g of aminophthalic acid was added. After being stirred and dissolved, the mixture was transferred into a sealed reaction vessel, reacted at 100 ° C for 24 h, and centrifuged. The precipitated product was washed with 500 mL of DMF and 500 mL of ethanol, and finally dried in vacuum at room temperature to obtain a multi-metal MOFs material with Cu / Zr / Mn as the metal center.
[0059] S2, dissolving 1-alkyl-3-methylimidazolium chloride ionic liquid in ethanol to prepare an ionic liquid ethanol solution with a concentration of 4 g / 100 mL, then adding 40 mL of the above ionic liquid ethanol solution to 100 g of the multi-metal MOFs material, sealing the container, placing it in a 70° C. water bath, shaking and reacting for 24 hours, taking it out, blowing off the remaining liquid with nitrogen, and obtaining a composite material;
[0060] S3, 0.5 kg of activated alumina and 0.3 kg of porous activated carbon were mixed, ethanol was added in a ratio of 100 g: 100 mL, the container was sealed, and placed in a 40°C water bath, shaken and soaked for 24 hours, taken out, and the remaining liquid was blown off with nitrogen to obtain a mixture;
[0061] S4. Add the composite material and the mixture into a mixer in a mass ratio of 1:3, mix them evenly, bake them at 120° C. under nitrogen protection for 2 h, and cool them naturally under nitrogen protection to obtain a mixed adsorbent of the MOFs ionic liquid composite material.
[0062] Figure 2 This is the SEM image of the multi-metal MOFs material with Cu / Zr / Mn as the metal center prepared in Example 1.
[0063] Figure 3 This is a thermogravimetric analysis (TGA) graph of the mixed adsorbent of the MOFs ionic liquid composite material prepared in Example 1.
[0064] Example 2
[0065] Preparation of MOFs ionic liquid composites:
[0066] S1, 100g Cu(NO 3 ) 2 ·3H 2 O, 80g Mn(NO 3 ) 2 ·4H 2 O and 30 g ZrCl 4After being mixed evenly, the mixture was dissolved in a mixed solution of 500 mL of hydrochloric acid solution (0.01 mol / L) and 500 mL of DMF, and then 60 g of aminophthalic acid was added. After being stirred and dissolved, the mixture was transferred into a sealed reaction vessel, reacted at 100 ° C for 24 h, and centrifuged. The precipitated product was washed with 500 mL of DMF and 500 mL of ethanol, and finally dried in vacuum at room temperature to obtain a multi-metal MOFs material with Cu / Zr / Mn as the metal center.
[0067] S2, dissolving 1-alkyl-benzimidazole chloride ionic liquid in ethanol to prepare an ionic liquid ethanol solution with a concentration of 4 g / 100 mL, then adding 50 mL of the ionic liquid ethanol solution to 100 g of the multi-metal MOFs material, sealing the container, placing it in a 65° C. water bath, shaking and reacting for 24 hours, taking it out, blowing off the remaining liquid with nitrogen, and obtaining a composite material;
[0068] S3, 0.5 kg of activated alumina and 0.5 kg of porous activated carbon were mixed, ethanol was added in a ratio of 100 g: 100 mL, the container was sealed, and placed in a 40°C water bath, shaken and soaked for 24 hours, taken out, and the remaining liquid was blown off with nitrogen to obtain a mixture;
[0069] S4. Add the composite material and the mixture into a mixer in a mass ratio of 1:4 and mix them evenly. Bake at 80° C. for 2 h under nitrogen protection and cool naturally under nitrogen protection to obtain a mixed adsorbent of the MOFs ionic liquid composite material.
[0070] Example 3
[0071] Compared with Example 1, the difference is that in step S4, the composite material and the mixture are added to the mixer and mixed according to the mass ratio of 1:1, 1:2, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.
[0072] Comparative Example 1
[0073] Preparation of MOFs ionic liquid composites:
[0074] S1. Dissolve 1-alkyl-3-methylimidazolium chloride ionic liquid in ethanol to prepare an ionic liquid ethanol solution with a concentration of 4 g / 100 mL, then add 40 mL of the above ionic liquid ethanol solution to 100 g of MOFs material (containing a single Zr metal), seal the container, put it in a 70° C. water bath, shake and react for 24 hours, take it out, blow off the remaining liquid with nitrogen, and obtain a composite material;
[0075] S2, 0.5kg activated alumina (particle size 10-40μm, specific surface area 60-90m 2 / g) and 0.3kg porous activated carbon (porosity 0.6-0.9cm 3 / g, particle size of 0.2-0.5mm), add ethanol in a ratio of 100g:100mL, seal the container, put it in a 40°C water bath, shake and soak for 24h, take it out, blow off the remaining liquid with nitrogen, and obtain a mixture;
[0076] S3. Add the composite material and the mixture into a mixer in a mass ratio of 1:3, mix them evenly, bake them at 120° C. under nitrogen protection for 2 h, and cool them naturally under nitrogen protection to obtain a mixed adsorbent of the MOFs ionic liquid composite material.
[0077] Comparative Example 2
[0078] Preparation of MOFs ionic liquid composites:
[0079] S1, 100g Cu(NO 3 ) 2 ·3H 2 O, 60g Mn(NO 3 ) 2 ·4H 2 O and 20 g ZrCl 4 After being mixed evenly, the mixture was dissolved in a mixed solution of 500 mL of hydrochloric acid solution (0.01 mol / L) and 500 mL of DMF, and then 90 g of aminophthalic acid was added. After being stirred and dissolved, the mixture was transferred into a sealed reaction vessel, reacted at 100 ° C for 24 h, and centrifuged. The precipitated product was washed with 500 mL of DMF and 500 mL of ethanol, and finally dried in vacuum at room temperature to obtain a multi-metal MOFs material with Cu / Zr / Mn as the metal center.
[0080] S2, dissolving 1-alkyl-3-methylimidazolium chloride ionic liquid in ethanol to prepare an ionic liquid ethanol solution with a concentration of 4 g / 100 mL, then adding 40 mL of the above ionic liquid ethanol solution to 100 g of the multi-metal MOFs material, sealing the container, placing it in a 70° C. water bath, shaking and reacting for 24 hours, taking it out, blowing off the remaining liquid with nitrogen, and obtaining a composite material;
[0081] S3, 0.5kg alumina (particle size 10-40μm, specific surface area 60-90m 2 / g) and 0.3kg activated carbon (porosity 0.6-0.9cm 3 / g, particle size of 0.2-0.5mm), add ethanol in a ratio of 100g:100mL, seal the container, put it in a 40°C water bath, shake and soak for 24h, take it out, blow off the remaining liquid with nitrogen, and obtain a mixture;
[0082] S4. Add the composite material and the mixture into a mixer in a mass ratio of 1:3, mix them evenly, bake them at 120° C. under nitrogen protection for 2 h, and cool them naturally under nitrogen protection to obtain a mixed adsorbent of the MOFs ionic liquid composite material.
[0083] Comparative Example 3
[0084] Preparation of MOFs ionic liquid composites:
[0085] S1, 100g Cu(NO 3 ) 2 ·3H 2 O, 60g Mn(NO 3 ) 2 ·4H 2 O and 20 g ZrCl 4 After being mixed evenly, the mixture was dissolved in a mixed solution of 500 mL of hydrochloric acid solution (0.01 mol / L) and 500 mL of DMF, and then 90 g of aminophthalic acid was added. After being stirred and dissolved, the mixture was transferred into a sealed reaction vessel, reacted at 100 ° C for 24 h, and centrifuged. The precipitated product was washed with 500 mL of DMF and 500 mL of ethanol, and finally dried in vacuum at room temperature to obtain a multi-metal MOFs material with Cu / Zr / Mn as the metal center.
[0086] S2, dissolving tetraethylammonium hexafluorophosphate ionic liquid in ethanol to prepare an ionic liquid ethanol solution with a concentration of 4 g / 100 mL, then adding 40 mL of the ionic liquid ethanol solution to 100 g of the multi-metal MOFs material, sealing the container, placing it in a 70° C. water bath, shaking and reacting for 24 hours, taking it out, blowing off the remaining liquid with nitrogen, and obtaining a composite material;
[0087] S3, 0.5kg activated alumina (particle size 10-40μm, specific surface area 60-90m 2 / g) and 0.3kg porous activated carbon (porosity 0.6-0.9cm 3 / g, particle size of 0.2-0.5mm), add ethanol in a ratio of 100g:100mL, seal the container, put it in a 40°C water bath, shake and soak for 24h, take it out, blow off the remaining liquid with nitrogen, and obtain a mixture;
[0088] S4. Add the composite material and the mixture into a mixer in a mass ratio of 1:3, mix them evenly, bake them at 120° C. under nitrogen protection for 2 h, and cool them naturally under nitrogen protection to obtain a mixed adsorbent of the MOFs ionic liquid composite material.
[0089] Test example
[0090] Figure 4This is the gas chromatography hydrogen flame ionization detector chromatogram of the standard solution of volatile ester compounds, 1: methyl formate, 2: ethyl formate, 3: 1,4-butyrolactone, 4: methyl acetate, 5: ethyl acetate, 6: propyl acetate, 7: butyl acetate, 8: pentyl acetate.
[0091] The mixed adsorbent of the MOFs ionic liquid composite material prepared in Examples 1 to 3 and Comparative Examples 1 to 3, the composite material in step S2 of Example 1, and the mixture in step S3 of Example 1 were used as adsorption materials to prepare a volatile ester compound adsorbent, and the steps are as follows:
[0092] The adsorbent material is loaded into a thermal desorption glass tube with a length of 160 mm, an inner diameter of 4 mm, and an outer diameter of 6 mm, which is previously filled with glass wool. The amount of adsorbent filled is 150 mg. Then a small amount of glass wool is loaded. Finally, rubber caps are put on both ends to obtain a volatile ester compound adsorbent, such as Figure 1 shown.
[0093] The volatile ester compound gas used for the adsorption capacity test in the following experiment was prepared as follows: 0.050 g of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate and 1,4-butyrolactone were accurately weighed into 8 1L polytetrafluoroethylene gas collecting bags, and then filled with nitrogen until full.
[0094] The composite volatile ester compound gas used for the adsorption efficiency test in the following experiment was prepared as follows: 10.0 mg and 15.0 mg of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate and 1,4-butyrolactone were accurately weighed and mixed in equal mass ratios, respectively, and added into two polytetrafluoroethylene gas collection bags with volumes of 1 L and 10 L, and then filled with nitrogen until full.
[0095] The adsorption capacity and adsorption efficiency of the volatile ester compound adsorbent prepared above were tested respectively, and the test temperature was 30°C and the humidity was 80% RH. The instrument used for the determination was an Agilent 7890 gas chromatograph with a split-splitless inlet and a hydrogen flame ionization detector, and was equipped with a Tekmar 6000 thermal desorber. Instrument conditions: Tekmar 6000 thermal desorber: desorption carrier gas flow rate: 43ml / min; pre-purge: 1min, sample tube desorption temperature: 220°C; desorption time: 10min; desorption temperature: 225°C, desorption time: 3min, baking temperature: 230°C, baking time: 10min. Chromatographic conditions: chromatographic column: HP-5 capillary column (30m×0.53mm). Carrier gas: nitrogen; carrier gas pressure before column: 105 kPa; programmed temperature rise: 0→0.5 min, 100°C; 0.5→3.5 min, heating rate 30°C / min, 100→190°C; 3.5→5.0 min, heating rate 20°C / min, 190→210°C; 5.0→7.0 min, maintain 210°C.
[0096] Among them, the penetration capacity (per 100 g) of the volatile ester compound adsorbent prepared from the material of Example 1 for adsorbing methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate, and 1,4-butyrolactone is shown in Table 1.
[0097] Table 1
[0098] Methyl formate Ethyl formate Methyl acetate Ethyl acetate Penetration capacity (mg) 3.1 14.5 7.6 31.2 Propyl acetate Butyl acetate Amyl acetate 1,4-Butyrolactone Penetration capacity (mg) 29.6 41.3 29.2 4.8
[0099] It can be seen from the data in Table 1 that the penetration capacities of the volatile ester compound adsorbent prepared by Example 1 of the present invention for different volatile ester compounds are: methyl formate 3.1 mg, ethyl formate 14.5 mg, methyl acetate 7.6 mg, ethyl acetate 31.2 mg, propyl acetate 29.6 mg, butyl acetate 41.3 mg, pentyl acetate 29.2 mg, 1,4-butyrolactone 4.8 mg. It is significantly better than the penetration capacities given by the adsorbent reported in the literature (GBZ160.63-2007), which are: methyl formate (2.1 mg), ethyl formate (8.4 mg), methyl acetate (2.9 mg), ethyl acetate (14.6 mg), propyl acetate (24.5 mg), butyl acetate (32.1 mg), pentyl acetate (21.0 mg), 1,4-butyrolactone (1.2 mg).
[0100] The adsorption efficiency experiment of the volatile ester compound adsorbent prepared by Example 1 and Example 2 was conducted using the composite volatile ester compound, and the test was carried out according to the test method and chromatographic conditions described above, and the results are shown in Table 2. It can be seen from the data in Table 2 that the adsorption efficiency of the volatile ester compound collected in the atmospheric environment using the mixed adsorbent of the present invention at two different concentrations can reach more than 92.0%.
[0101] Table 2
[0102]
[0103] The adsorption efficiency of the volatile ester compound adsorbent prepared in Example 1 and Example 3 was tested using the composite volatile ester compound according to the test method and measurement conditions described above. The results are shown in Table 3.
[0104] Table 3
[0105]
[0106] It can be seen from the data in Table 3 that when the mass ratio of the MOF ionic liquid composite material to the alumina-activated carbon mixture is in the range of 1:1 to 1:6, the adsorption efficiency of the mixed adsorbent for volatile ester compounds is greater than 90%. When the mass ratio is 1:7 to 1:10, the adsorption efficiency of the mixed adsorbent for volatile ester compounds decreases to between 75.2% and 87.5%.
[0107] The adsorption efficiency test of the volatile ester compound adsorbent prepared by Example 1 and Comparative Examples 1 to 3, as well as the composite material of step S2 and the mixture of step S3 in Example 1 was conducted using the composite volatile ester compound. The results are shown in Table 4.
[0108] Table 4
[0109]
[0110] It can be seen from the data in Table 4 that the difference between Comparative Example 1 and Example 1 is mainly the difference in MOFs materials. Example 1 uses a multi-metal MOFs material with Cu / Zr / Mn as the metal center, while Comparative Example 1 uses a MOFs material containing a single metal Zr. Due to the differences in metal nodes and spatial structures in MOFs, the adsorption efficiency is different. In Comparative Example 2 and Example 1, the components of the MOFs material, alumina and activated carbon in the mixed adsorbent are the same, and only the composition ratio is different. Comparative Example 2 obtains a better adsorption efficiency. The difference between Comparative Example 3 and Example 1 is mainly the difference in ionic liquids. Example 1 uses 1-alkyl-3-methylimidazolium chloride ionic liquid, while Comparative Example 3 uses tetraethylammonium hexafluorophosphate ionic liquid, that is, non-nitrogen heterocyclic ionic liquid, which leads to differences in adsorption efficiency. If only the composite material of step S2 in Example 1 is used as an adsorbent for volatile ester compounds, the adsorption efficiency is 80.7%, and the ideal adsorption effect cannot be achieved. If only the mixture in step S3 of Example 1 is used as the adsorbent for volatile ester compounds, the adsorption efficiency is only 54.5%, and the ideal adsorption effect cannot be obtained either.
[0111] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0112] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a multi-metal MOFs material, characterized in that the steps include: Cu 2+ , Mn 2+ and Zr 4+ The multi-metal MOFs material is obtained by using aminophthalic acid as an organic ligand to coordinate the metal through a solvent thermal reaction.
2. The preparation method according to claim 1, characterized in that The Cu 2+ , Mn 2+ and Zr 4+ The molar ratio is 1:0.5-1.2:0.05-0.4; and / or, The Cu 2+ At least one of nitrate, hydrochloride, sulfate and acetate derived from copper; and / or, The Mn 2+ At least one of the nitrate, sulfate, hydrochloride and acetate of manganese; and / or, The Zr 4+ At least one of zirconium hydrochloride, zirconium acetate, zirconium nitrate and zirconium hydroxide; and / or, The molar ratio of the organic ligand to the coordination metal is 1:0.5-3.0; and / or, The temperature of the solvent thermal reaction is 60-100° C. and the time is 12-24 hours.
3. A multi-metal MOFs material, characterized in that: The multi-metal MOFs material is prepared by the preparation method described in claim 1 or 2.
4. A MOFs ionic liquid composite material, characterized in that: The raw material includes the multi-metal MOFs material as described in claim 3.
5. A method for preparing the MOFs ionic liquid composite material according to claim 4, characterized in that the steps include: The multi-metal MOFs material and the ethanol solution of the ionic liquid are uniformly mixed, reacted, and nitrogen blown to obtain a composite material; The activated alumina and activated carbon are uniformly mixed, and then ethanol is added, soaked, and nitrogen blown to obtain a mixture; The composite material and the mixture are uniformly mixed, and the MOFs ionic liquid composite material is obtained through baking and cooling.
6. The preparation method according to claim 5, characterized in that: The ratio of the multi-metal MOFs material to the ethanol solution of the ionic liquid is 100 g: 20-100 mL; and / or, The concentration of the ionic liquid in the ethanol solution of the ionic liquid is 1 to 5 g / 100 mL; and / or, The ionic liquid in the ethanol solution of the ionic liquid is a nitrogen-containing heterocyclic ionic liquid.
7. The preparation method according to claim 6, characterized in that: The nitrogen-containing heterocyclic ionic liquid includes at least one of 1-alkyl-3-methylimidazolium chloride, 1-alkyl-1,2,4-triazole sulfate, 1-alkyl-benzimidazole chloride and 1-pentyl-1,2,3-benzotriazole sulfate.
8. The preparation method according to claim 5, characterized in that: The reaction is carried out by shaking at 60-80°C for 12-24h; and / or, The mass ratio of activated alumina to activated carbon is 0.2-1:0.1-2; and / or, The particle size of the activated alumina is 10-40 μm; and / or, The porosity of the activated carbon is 0.6-0.9 cm 3 / g, with a particle size of 0.2-0.5 mm; and / or, The mass / volume ratio of the sum of the mass of the activated alumina and the activated carbon to the mass of ethanol is 100g / 20-100mL; and / or, The soaking treatment is performed by shaking and soaking at 30-50° C. for 12-24 hours; and / or, The mass ratio of the composite material to the mixture is 1:1-5; and / or, The baking temperature is 50-150° C. and the baking time is 1-3 hours.
9. Use of the multi-metal MOFs material according to claim 3 or the MOFs ionic liquid composite material according to claim 4 in the adsorption of volatile ester compounds.
10. A volatile ester compound adsorbent, characterized in that: The raw material includes the MOFs ionic liquid composite material according to claim 4.